Bidirectional three phase power converter - Alias, A.; Rahim, N.A.; Hussain, Mohd Azlan (2011)
This research aimed to design a three-phase ac-dc buck converter to achieve low-THD unity-power-factor sinusoidal input current and regulated dc voltage via modified pulse-width-modulation (PWM) technique. A 6-switch topology with bidirectional power flow capability is presented. The modified PWM switching strategy is discussed and verified via Matlab-Simulink and implemented in Digital Signal Processor (DSP) TMS320F28335. The topology and the switching technique performed well for sinusoidal input current, power factor, harmonic distortion level of the ac input currents, and regulated dc voltage, and enabled return of power flow from the dc side back to the ac. Simulation using Matlab-Simulink is presented to verify the effectiveness of the circuit configuration.